KEEFEKTIFAN KEEFEKTIFAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS MAHASISWA - Wijayanti, Palupi Sri (APOTEMA : Jurnal Program Studi Pendidikan Matematika, 2018)
The aim of this study is to describe the effectiveness of the use of Cooperative Script model in linear algebra teaching and learning at base of  vector space chapter which is viewed by students mathematical reasoning skill. The type of this research is experimental research. The design of experimental research is pre experimental research. Because of the aim of this study is to determine whether Cooperative Script model can effect in students mathematical reasoning skill or not, so this study uses one group pretest posttest design. The population in this study is all of Mathematics Educationsâ students in UPY and the sample are class in A1 and A2. Sampling technique used simple random sampling technique. The instrument used questions in pretest and posttest test which are to know the scores of studentsâ mathematical reasoning skill at beginning and the end of teaching and learning process. Data analysis techniques used descriptive statistics analysis and inferential statistics analysis. Descriptive statistics analysis is used to know the mean, mode, and variance of scores. Inferential statistics analysis used normality test and t test. The results showed that the scores which obtaned after learn linear algebra using cooperative script model such as the highest score is 97.90, the lowest score is 48.33, the average score is 78.08, and the standard deviation 13.83. The result of normality test on pretest and posttest score with chi-square test showed that c2 htung < c2 table. This result showed that the all of data in pretest and postest scores are normally distributed with 95% confidence level. The result of t-test showed that H0 is rejected with 95% confidence level. Thus, it can be infered that there is a significant increase in students mathematical reasoning skills before and after learn with cooperative script model. 83% categorization of studentsâ mathematical reasoning skill at high and moderat category indicated that cooperative script model effective in terms of students mathematical reasoning skills.